2020
DOI: 10.1016/j.ajog.2020.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Fetal molding examined with transperineal ultrasound and associations with position and delivery mode

Abstract: 10/27 (37%); p=0.04. In OA positions the molding was seen as occipito-parietal molding in 68/69 cases, and as parieto-parietal molding in one case with deflexed attitude. Molding was seen in 19/38 (50%) of OA positions ending with spontaneous delivery, 42/71(59%) ending with vacuum extraction and in 7/8 (88%) with failed vacuum extraction (p=0.13). In four fetuses with OP positions parieto-parietal molding was diagnosed and successful vacuum extraction occurred in three cases and failed extraction in one. Fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The skull bones overlap during the passage through the birth canal and the fetal head becomes molded. 66 Because of molding, the leading bony part of the skull may be HSD, head-symphysis distance.…”
Section: Head-symphysis Distancementioning
confidence: 99%
“…The skull bones overlap during the passage through the birth canal and the fetal head becomes molded. 66 Because of molding, the leading bony part of the skull may be HSD, head-symphysis distance.…”
Section: Head-symphysis Distancementioning
confidence: 99%
“…10,24 Reshaping of the fetal skull is possible because the skull bones can overlap. 11 During this process the fetal head gets elongated with increased longitudinal diameter and reduced transverse diameter, increasing the probability of a vaginal delivery. 25 We found longer heads in fetuses in active labor than those examined before the start of active phase.…”
Section: Clinical Significancementioning
confidence: 99%
“…In flexed occiput anterior (OA) position, fetal head engagement occurrs when the leading bony part of the skull is at the level of the ischial spines. 7e9 In malpositions and molded (reshaped) fetal heads, the leading bony part of the skull may be below the ischial spines when the largest diameter of the fetal skull is still above the pelvic inlet, 10,11 An attempt at assisted vaginal birth in such a situation would be associated with risks of maternal and neonatal complications, and therefore, contraindicated in modern obstetrics. To avoid this mismanagement, a vaginal or transperineal assessment of fetal head descent should be supplemented with abdominal examination, as recommended in several guidelines and the World Health Organization partograph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active management of labor dystocia typically includes calculating adequacy of uterine contractions using Montevideo units (MVUs) measured via an intrauterine pressure catheter [ 2 ]. Studies have found that the inclination of the pelvis and uterus in the birth canal is also an influential factor in dystocia [ 3 ]. Uterine inclination is an important factor for birth canals and fetuses in vaginal delivery [ 4 ].…”
Section: Introductionmentioning
confidence: 99%